Genetic analysis and agronomic performance of local rice genotypes under salinity stress - Rashid, Md Mamunur; Ferdoush, Ashrafi; Hassan, Lutful; Begum, Shamsun Nahar (Fundamental and Applied Agriculture, 2017)
Ten rice genotypes including seven landraces and three released varieties were used as plant material to study genetic divergence using multivariate analysis. Ten genotypes fell into three distinct clusters. The distribution pattern revealed maximum number of genotypes in cluster I and III while cluster II included minimum number of genotypes. The inter-cluster distances in all of the cases were higher than that of intra-cluster distances suggesting wider genetic diversity among the genotypes of different clusters. The intra-cluster distances in all the three clusters were low indicating the genotypes within the same clusters were closely related. Maximum genetic distance was observed between cluster I and cluster III. The genotype of cluster I with the cumulative ranking 1, for those traits like days to maturity, days to 50% flowering, plant height, panicle length, number of filled grains panicle-1, Fertility percent and yield panicle-1. In case of principal component analysis the first three components of the principal component with eigen values >1 contributed 83.00 percent variability existing in the rice genotypes for yield contributing traits in the study. Thus the results of principal component analysis revealed, wide genetic variability exists in this rice germplasm accessions. High salt tolerant traits with high genetic variability are expected to provide high level of gene transfer during breeding programs.